THE ROLE OF MANAGEMENT IN ON EDGE OF XXI CENTURY - Klepacki, Bogdan; Gołębiewska, Barbara (Acta Scientiarum Polonorum. Oeconomia, 2002)
In the paper has been presented the rule of management in economic and civilization development on the level of microeconomics in separate enterprises or organization as well as macroeconomic - whole society. There was made the analysis in tendency of change in management, in development of theory organization and management and the challenge for management on edge of XXI century.